2010
DOI: 10.1590/s0101-20612010000200018
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade oxidativa e sensorial de farinhas de trigo e fubá irradiados

Abstract: Um aumento no índice de peróxido diretamente proporcional à radiação absorvida por grãos foi observado por Hanis et al. (1988), entretanto, mesmo pertencendo à classe dos constituintes de alimentos mais sensíveis à irradiação, em doses superiores a 10 kGy, não se observou alteração significativa nos lipídios dos cereais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
1
0
3
Order By: Relevance
“…Similar results were found by Silva et al (2010), who evaluated the oxidative stability in irradiated wheat flour and cornmeal, and who observed a significant increase in moisture in the samples from the first 30 days onwards. Marathe et al (2002) found that moisture levels in irradiated and non-irradiated wheat flour increased at 120 days of storage.…”
Section: Effects Of Gamma Radiation On Physicochemical and Microbiolosupporting
confidence: 88%
“…Similar results were found by Silva et al (2010), who evaluated the oxidative stability in irradiated wheat flour and cornmeal, and who observed a significant increase in moisture in the samples from the first 30 days onwards. Marathe et al (2002) found that moisture levels in irradiated and non-irradiated wheat flour increased at 120 days of storage.…”
Section: Effects Of Gamma Radiation On Physicochemical and Microbiolosupporting
confidence: 88%
“…Portanto, o fato de ter sido empregada embalagem de polipropileno para armazenagem das farofas pode ter influenciado de forma positiva na prevenção da oxidação lipídica. Silva et al (2010) avaliaram os efeitos de diferentes doses de radiação gama em farinha de trigo e fubá armazenadas por 3 e 6 meses, respectivamente, e não foi encontrada nenhuma presença de peróxidos durante o tempo de armazenagem, assim como neste trabalho. A ausência de peróxidos durante a armazenagem atribuiu às farofas temperadas à base de okara desidratado um tempo satisfatório de vida de prateleira, semelhante ao de farofas comerciais, que varia de 4 a 6 meses.…”
Section: Resultsunclassified
“…Alcoholic acidity was determined according to IS:1155-1968 [40] after 13, 66 and 129 days of storage since it is used as a flour freshness indicator. Finally, the peroxide index, evaluated as an indicator of the rancid degree of the flours, followed the method described by Silva et al [41] and was assessed after 41, 66 and 129 days of storage. All the tests were performed in duplicate.…”
Section: Flour Quality Evaluationmentioning
confidence: 99%